##### Ads

related to: sec

**sec**^2(18) - tan^2(18) First off, remember that there is an identity that relates**sec**^2(x) with tan^2(x); it goes**sec**^2(x) = tan^2(x) + 1. Therefore...6 Answers Â· Science & Mathematics Â· 13/03/2007

Triple

**Sec**can be considered a generic and inexpensive version of Cointreau. ... the amount for Cointreau as compared Triple**Sec**, you should.10 Answers Â· Food & Drink Â· 24/02/2007

I have lost respect for the

**SEC**due to its extremly weak non-conference scheduling...if you factor beating the cupcakes of the**SEC**(Miss & Miss St.) thats 6...16 Answers Â· Sports Â· 31/08/2007

âŒ

**sec**^3(x)dx = âŒ**sec**(x)**sec**^2(x)dx u=**sec**x du=**sec**(x)tan(x)dx dv=**sec**^2(x)dx v = tan(x) âŒ**sec**^3(x)dx =**sec**(x...x)- âŒ (**sec**^2(x)-1)**sec**(x)dx âŒ**sec**^3(x)dx =**sec**(x)tan(x)- âŒ (**sec**^2(x)**sec**(x)dx + âŒ**sec**(x)dx transpose âŒ (**sec**^2(x)**sec**(x)dx to...3 Answers Â· Science & Mathematics Â· 20/03/2011

Since

**sec**Î¸ = 1/cosÎ¸, consider the sign of cosÎ¸ (since**sec**Î¸ and cosÎ¸ will have the...cosÎ¸ < 0 in Quadrants II and III,**sec**Î¸ < 0 in Quadrants II and III as...1 Answers Â· Science & Mathematics Â· 23/08/2011

âˆ«

**sec**^2(x) dx multiply and divide with tan x âˆ«tan x**sec**^2(x) dx / tan x let tan x = u**sec**^2(x) dx = du now the integral becomes...5 Answers Â· Science & Mathematics Â· 03/01/2010

I = âˆ«

**sec**^n(x) dx = âˆ«**sec**^(n-2)(x)**sec**^2(x) dx = âˆ«**sec**^(n-2)(x) dtan(x) =**sec**^(n-2)(x) tan(x) - âˆ«tan(x) (n-2)**sec**^(n-2) tan(x) dx =**sec**^(n-2)(x) tan(x) - âˆ«(n-2)**sec**^(n-2) tan^2(x) dx =**sec**^(n-2...3 Answers Â· Science & Mathematics Â· 05/02/2011

âˆ«

**sec**(x) tan^4(x) dx For the integrand tan^4(x)**sec**(x), use the trigonometric identity tan^2(x) =**sec**^2(x)-1... the reduction formula, âˆ«**sec**^m(x) dx = (sin(x)**sec**^(m-1)(x))/(m-1) + (m-2)/(m-1) âˆ«**sec**^(-2+m)(x) dx, where...2 Answers Â· Science & Mathematics Â· 25/10/2010

1.)

**sec**^ 4 -**sec**^ 2 = tan^ 4 + tan^ 2 =**sec**^2x(**sec**^2x-1) =**sec**^2xtan^2x =(1+tan^2x)(tan^2x) =tan^2x+tan^4x answer// 2.) (tan(a...sin^2(a)cos^2(a) ......1..............1 =------------- - ------------- ....cos^2a......sin^2(a) =**sec**^2(a)-csc^2(a) answer//3 Answers Â· Science & Mathematics Â· 21/03/2009

**sec**(x) * dx =>**sec**(x) * (**sec**(x) + tan(x)) * dx / (**sec**(x) + tan(x)) => (**sec**(x)^2 * dx +**sec**(x) * tan(x) * dx) / (**sec**(x) + tan(x)) u =**sec**(x) + tan(x) du =**sec**(x) * tan(x) * dx +**sec**(x)^2 * dx du / u ...4 Answers Â· Science & Mathematics Â· 17/04/2013

##### Ads

related to: sec